Оцінка ефективності цифрової трансформації в управлінні бізнес-процесами агропромислових підприємств - Лисенко, Сергій Миколайович (Міжнародний університет бізнесу і права, 2025)
У статті розроблено комплексний методичний підхід до оцінювання ефективності цифрової трансформації управління бізнес-процесами агропромислових підприємств. Обґрунтовано інтеграцію ключових показників ефективності з моделлю зрілості управління бізнес-процесами для кількісного вимірювання рівня цифрової зрілості. Цифрову трансформацію розглянуто як безперервний багатовимірний процес, що охоплює технологічні, організаційні та культурні аспекти управління. Визначено ключові чинники: автоматизацію процесів, управління даними, лідерство, розвиток цифрової культури та орієнтацію на сталий розвиток. Підхід передбачає узгодження цифрових ініціатив із принципами ESG та ЦСР, спрямованими на забезпечення ефективності, прозорості й конкурентоспроможності агропромислових підприємств у контексті зеленої трансформації. The article develops a comprehensive methodological framework for assessing the effectiveness of digital transformation in business process management within Agri-industrial enterprises. The study substantiates the integration of key performance indicators with the Business Process Management Maturity Model to provide a structured and measurable basis for evaluating digital maturity. The relevance of this research is determined by the growing need to enhance process efficiency, data integrity, innovation capacity, and sustainability in agricultural production under the influence of global digitalization, environmental transformation, and the green transition. The proposed framework conceptualizes digital transformation as a continuous, multidimensional, and iterative process that unites technological, organizational, and cultural dimensions of business management. It considers digital transformation not only as a technological upgrade but as a strategic shift that influences corporate governance, value creation, and long-term competitiveness. The framework identifies five interrelated dimensions: process standardization and automation, data governance and analytical capability, human capital and leadership readiness, technological infrastructure, and sustainability orientation. Each dimension reflects specific maturity indicators that enable quantitative and qualitative assessment of an enterprise’s digital progress. The study emphasizes the interdependence between process automation, leadership involvement, innovation management, and the establishment of a data-driven culture as fundamental enablers of transformation. It highlights the role of digital literacy, cross-departmental collaboration, and management adaptability in achieving meaningful transformation outcomes. The approach also reflects the systemic integration of ESG principles and sustainable performance metrics into management evaluation, ensuring that technological modernization contributes to both environmental and social objectives. By aligning digital initiatives with corporate social responsibility and green innovation strategies, the framework provides a balanced perspective that connects efficiency gains with long-term resilience, transparency, and competitive advantage. The developed model serves as both a diagnostic and strategic management tool, enabling enterprises to identify inefficiencies, benchmark maturity levels, and design targeted improvement programs. Furthermore, it facilitates evidence-based decision-making, and the formulation of digital development roadmaps aligned with the UN Sustainable Development Goals. The proposed approach can be used by policymakers, analysts, and corporate managers to monitor digital transformation dynamics, evaluate return on digital investments, and develop governance systems that ensure adaptability under rapidly changing technological and market conditions. Ultimately, the framework promotes the creation of digitally mature, innovative-oriented, and environmentally responsible Agri-industrial ecosystems capable of maintaining sustainable growth and competitiveness in the global digital economy.
Evaluating the effectiveness of digital transformation in agri-industrial business process management
Keywords: цифрова трансформація; управління бізнес-процесами; оцінка впливу; показники KPI; зрілість процесів; сталий розвиток; digital transformation; business process management; impact assessment; KPI indicators; process maturity; sustainable development